Successful Robotic Enucleation of a Rare Bladder Leiomyoma Through a Trans-Vesical Route: A Novel Surgical Approach - Giacomo Rebez; Serena Sartori; Fabio Vianello; Elena Marcotti; Rossana Bussani; Giovanni Liguori; Filiberto Zattoni; Mariangela Mancini (Uro)
Background: Bladder leiomyomas are rare benign tumors (<0.5% of all bladder tumors) arising from the bladder wall’s smooth muscle. Only 250 cases of this condition have been reported worldwide so far. While some leiomyomas present with irritative or obstructive symptoms, hematuria, or nonspecific abdominal pain, others are asymptomatic and are diagnosed incidentally. The surgical approach is based on the leiomyoma’s size and location. Given this tumor’s rarity, standardized management guidelines do not exist; however, transurethral resection of bladder tumor (TURBT), partial or radical cystectomy, or laparoscopic/robotic enucleation are viable therapeutic options. Case history: We report the case of a 64-year-old female presenting with recurrent colic and pelvic pain. An abdominal CT scan showed a 3 cm mass protruding from the posterior bladder wall toward the right vaginal fornix. A transvaginal ultrasound-guided through-cut biopsy confirmed the diagnosis of a bladder leiomyoma. Due to the tumor’s size and location, robotic enucleation was chosen to minimize the risk of bladder perforation. The mass was successfully excised via a transvesical approach. Results: The procedure was completed in 210 min without complications, with 50 mL blood loss. The patient recovered well, with resolution of symptoms and no recurrence at eighteen-month follow-up. Histopathological examination on the surgical specimen confirmed the diagnosis of bladder leiomyoma. Conclusions: This case highlights the feasibility and safety of robotic enucleation for large bladder leiomyomas, emphasizing minimal invasiveness, limited pelvic dissection, and preservation of bladder function. Further research and standardized guidelines are needed for managing this rare condition.